New cross‐linkable poly[bis(octafluoropentoxy) phosphazene] biomaterials: Synthesis, surface characterization, bacterial adhesion, and plasma coagulation responses. Issue 8 (18th June 2020) - Xu, Li‐Chong; Chen, Chen; Zhu, Jieru; Tang, Meixian; Chen, Andy; Allcock, Harry R.; Siedlecki, Christopher A.
Abstract: Biomaterial‐associated microbial infection and thrombosis represent major issues to the success of long‐term use of implantable blood‐contacting medical devices. The development of new poly[bis(octafluoropentoxy) phosphazene (OFP) biomaterials provides new routes for combatting microbial infection and thrombosis. However, the limited mechanical properties of OFP to date render them unsuitable for application in medical devices and inhibit any attempts at subsequent surface topography modification. In this study, we synthesized cross‐linkable OFPs (X‐OFPs) with the different degrees of cross‐linking in an effort to improve the mechanical properties. The results showed that the surface chemistry and surface topography of X‐OFPs do not change significantly, but the surface mechanical stiffness increased after cross‐linking. Atomic force microscopic phase images showed that the polymer phase separation structures changed due to cross‐linking. Experiments with three bacterial strains: Staphylococcal epidermidis, Staphylococcal aureus, and Pseudomonas aeruginosa showed that bacterial adhesion was significantly decreased on the OFP and X‐OFPs for both the pre‐cross‐linked and cross‐linked as compared to polyurethane biomaterials. Furthermore, bacterial adhesions were lower on X‐OFP surfaces than on pre‐cross‐linked materials, suggesting that mechanical stiffness is an important parameter influencing bacterial adhesion. Blood plasma coagulation responses revealed longer coagulation times for OFP and X‐OFP materials than on polyurethanes, indicating that the new cross‐linked OFPs are resistant to plasma coagulation compared to currently used polyurethane biomaterials.